Recent progress of the single crystal growth of homologous (InGaO3)m(ZnO)n. Issue 25 (15th June 2022) - Kase, Naoki; Kimizuka, Noboru; Miyakawa, Nobuaki
Abstract : Crystal structure of the homologues series of (InGaZnO3 ) m (ZnO) n . Abstract : Compounds composed of In–Ga–Zn–O (IGZO) have characteristic homologous crystal structures represented by the following general formula: (InGaO3 ) m (ZnO) n . Such compounds have been applied in many fields since the discovery that amorphous oxide thin films have high electron mobility. On the other hand, very few studies have been conducted on single crystals or the bulk behavior of IGZO compounds as growing large crystals is difficult. Consequently, the physical properties have not been clarified. In this review, we summarize the historical background of IGZO regarding the crystal structure and crystal growth, and introduce our successful method for growing large single crystals of InGaZnO4 . We also introduce the micro-crystals of (InGaO3 )2 (ZnO)1 .